Переходные характеристики двухходового трубчатого теплообменного аппарата - Шевелев, Александр Александрович; Тарасенко, Александр Николаевич; Барвинок, В. С. (НТУ "ХПИ", 2011)
On the basis of numeral design the self-reactance analysis of transients of tubular two-thread heat-exchange vehicle isconducted. A heat-exchange vehicle isexamined as an object with distributive parameters. The executed decisions allowed to get transitional descriptions of heat-exchange vehicle depending on the rate of change of temperature of warming heat-carrying agent for the row of characteristic values of aquatic numbers of heat-carrying agents.
Keywords: воздухоподогреватель; численный эксперимент; дымовой газ; температура воздуха